Invisible audio: an analysis of the podcasts of Portuguese newspapers - Reis, Ana Isabel (2018)
Since the dawn of the internet, sound in journalistic content has assumed a secondary, ancillary role. Under-use of sound within the context of cyber-journalism has been recognised by academics and professionals. It appears that Portuguese newspapers have only recently realised the full potential of sound, as they have begun to produce exclusive sound content, distributed via podcasts. This study focuses on three Portuguese generalist newspapers (Público, Expresso and Observador), which are the only newspapers where updated podcasts were found. The text will analyse the sound products available in the respective websites of these three newspapers, and in their Soundcloud and iTunes accounts. It aims to classify the audio contained in the podcasts of these publications, in order to understand how a newspaper develops sound products in a digital environment and whether they contain distinctive elements that may reveal a distinct identity. Given the possibilities of using audio and podcasts, one of the conclusions of this study is that after an initial period of rather timid investment in audio content, and following various advances and setbacks over the last decade, Portuguese newspapers have finally begun to make a firm commitment to sound production, albeit on an exploratory basis and in a form that is very similar to radio.